(untitled) (Journal of Medicine, 2021)
We report the case of a 30-year-old normotensive, nondiabetic lady diagnosed case of Systemic Lupus Erythematosus(SLE); who came with the complaints of limb claudication. After clinical and lab evaluation she was diagnosed as a case of Takayasus Arteritis along with SLE. Though the co- existence of SLE and Takayasu’s Disease is very rare, we should search for the development of arterial occlusive diseases in SLE cases if the patient has got suspicious symptoms. J MEDICINE 2021; 22: 146-149